Multifunctional cuttlebone microneedle patch and preparation method thereof
By constructing a multifunctional cuttlebone microneedle patch and combining it with acetic acid gradient decalcification process and layered delivery technology, the problems of insufficient drug penetration in the traditional cuttlebone powder application form and the single antibacterial nature of the microneedle system were solved, achieving synergistic treatment of antibacterial, angiogenesis-promoting and anti-inflammatory effects, and significantly accelerating the healing process of diabetic wounds.
Patent Information
- Application Number
- CN202511145820.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-10-14
AI Technical Summary
In the current treatment of chronic diabetic wounds, the traditional cuttlebone powder topical application has insufficient drug penetration depth and rapid release defects, resulting in low bioavailability. In addition, the single antibacterial component of the traditional microneedle system is prone to drug resistance, and it is difficult to balance mechanical strength and drug sustained-release performance, and it cannot adapt to the dynamic exudate microenvironment.
A multifunctional cuttlebone microneedle patch is used, which consists of a needle body layer and a backing layer. The needle body layer is composed of cuttlebone decalcified powder, carboxymethyl chitosan/silver nanoparticle sol and methacrylated gelatin-dopamine pregel solution. It is combined with acetic acid gradient decalcification process and layered delivery technology to achieve synergistic antibacterial, angiogenic and anti-inflammatory treatment.
It significantly inhibits related bacteria, prolongs the antibacterial effect, promotes cell proliferation, migration and angiogenesis, and accelerates wound healing, promotes collagen deposition and vascular maturation, relieves inflammation, and improves the diabetic wound microenvironment both in vivo and in vitro.
Smart Images

Figure CN120771131A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical technology, and in particular to a multifunctional cuttlebone microneedle patch and a preparation method thereof. Background Art
[0002] Chronic diabetic wounds, characterized by complex pathological features such as oxidative stress, persistent inflammation, angiogenesis disorders, and susceptibility to infection induced by long-term hyperglycemia, collectively lead to delayed healing and a high risk of amputation, becoming a major challenge in global public health. The mechanisms by which wound healing is hindered involve multiple factors: a high-sugar microenvironment promotes bacterial biofilm formation, leading to enhanced antibiotic resistance; excessive inflammatory responses and accumulation of reactive oxygen species (ROS), disrupting cell migration and extracellular matrix (ECM) remodeling; and endothelial dysfunction, further exacerbating local hypoxia and insufficient nutrient supply. Although existing clinical therapies (such as debridement, hydrogel dressings, and topical application of growth factors) can partially alleviate symptoms, their low drug penetration efficiency, single target, and difficulty in dynamically regulating the wound microenvironment severely limit their therapeutic effectiveness.
[0003] In recent years, natural biomaterials have become a research hotspot due to their biocompatibility and pleiotropic properties. Cuttlebone (CB), a natural material from the ocean, is rich in calcium carbonate (CaCO 3, >90%) and chitin have been shown to possess significant hemostatic, coagulant, antibacterial, anti-inflammatory, and angiogenic activities, and are clinically used for wound healing and tissue regeneration, such as in the repair of diabetic foot ulcers, oral ulcers, acute and chronic eczema, and postoperative wounds. However, traditional powder topical applications often suffer from issues such as insufficient drug penetration and rapid release, resulting in low bioavailability and poor patient compliance, limiting their translational application in the treatment of DFUs.
[0004] Dissolvable microneedles (MNs) technology has shown great potential in the treatment of chronic wounds due to its advantages of painlessly penetrating the stratum corneum and precisely delivering drugs to deep tissues. However, traditional microneedle systems still face the following challenges: ① Single antimicrobial ingredients (such as silver nanoparticles) are prone to drug resistance and lack anti-inflammatory synergy; ② It is difficult to balance mechanical strength and drug sustained-release performance, and they cannot adapt to the dynamically changing microenvironment of diabetic wound exudate; ③ Natural active ingredients (such as traditional Chinese medicine extracts) have insufficient bioavailability due to low delivery efficiency. Therefore, the development of a multifunctional microneedle system that integrates high-efficiency antibacterial, anti-inflammatory, angiogenesis-promoting, and dynamic exudate management has become the key to breaking through the bottleneck of diabetic wound treatment. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide a multifunctional cuttlebone microneedle patch and a preparation method thereof. The multifunctional cuttlebone microneedle patch provided by the present invention has good biological activity and can release Ag in a time sequence. + The active ingredients can significantly inhibit related bacteria in vitro, prolong the antibacterial effect, and promote cell proliferation, migration and angiogenesis. In vivo results show that it can accelerate wound healing, promote collagen deposition and vascular maturation, and relieve inflammation.
[0006] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A multifunctional cuttlebone microneedle patch is made up of two parts: a needle body layer and a backing layer:
[0008] The needle body layer is composed of cuttlebone decalcified powder (CBP), carboxymethyl chitosan / argentum nanoparticles sol (CMCS / Ag NPs) and gelatin methacryloyl-dopamine (GelMA-DA) needle body pre-gel solution.
[0009] As a preferred embodiment, the backing layer in the multifunctional cuttlebone microneedle patch is composed of chitosan (CS), succinic acid (BDA), and dopamine (DA).
[0010] A method for preparing a multifunctional cuttlebone microneedle patch comprises the following steps:
[0011] Step 1: Preparation of the components of the needle body layer;
[0012] Step 2: Preparation of backing layer pregel solution;
[0013] Step 3: Preparation of multifunctional cuttlebone microneedle patch.
[0014] In the present invention, in the specific embodiments and effect experimental investigations, the preparation method of the components of the needle body layer in step 1 is:
[0015] Step 1.1: The cuttlebone is air-dried and crushed, soaked in an acid solution, and magnetically stirred until no bubbles are generated. The supernatant is discarded to obtain decalcified cuttlebone powder (CBP) with different decalcification degrees.
[0016] Step 1.2: Prepare AgNO3 solution in the dark, sonicate, and stir. Add carboxymethyl chitosan (CMCS) powder to the AgNO3 solution, stir, and cure with ultraviolet light to obtain carboxymethyl chitosan / silver nanoparticle sol, i.e., CMCS / Ag NPs sol.
[0017] Step 1.3: Dissolve dopamine DA powder and methacrylated gelatin GelMA powder in deionized water to obtain methacrylated gelatin-dopamine GelMA-DA needle pregel solution.
[0018] In some embodiments, the acid solution in step 1.1 is a glacial acetic acid solution with a concentration of 0.1 to 0.3 mol·L -1 ; The magnetic stirring speed is 300-800 r / min; The mass / volume ratio of cuttlebone to acid solution is 1:25-1:100.
[0019] In some embodiments, the acid solution in step 1.1 is a glacial acetic acid solution with a preferred concentration of 0.2 mol·L -1 ; The magnetic stirring speed is preferably 500r / min.
[0020] In some embodiments, the mass / volume ratio of the cuttlebone to the acid solution in step 1.1 is 1:25 to 1:100, preferably 1:50 or 1:75, in g / mL.
[0021] In some embodiments, the concentration of the AgNO3 solution in step 1.2 is 1×10 -3 ~3×10 -3 mol·L -1 ; preferably 2×10 -3 mol·L -1 The ultrasonic time is 30 min; the stirring time when preparing the AgNO3 solution is 4 h; the stirring time after adding the CMCS powder is 2 h; the curing environment temperature is below 40 ° C; the ultraviolet light is 365 nm, 100 m W·cm -2 UV light; the curing time is 30 minutes.
[0022] In some embodiments, the mass / volume ratio of the CMCS powder to the AgNO 3 solution in step 1.2 is 20:1 to 60:1, preferably 40:1, in mg / mL.
[0023] In some embodiments, in mg / mL, the mass / volume ratio of the DA powder to deionized water in step 1.3 is 16:1; the mass / volume ratio of the GelMA powder to deionized water is 50:1, 100:1, 150:1, 200:1, or 300:1, respectively, preferably 200:1.
[0024] In the present invention, in the specific embodiments and effect experimental investigations, the preparation method of the CS / BDA / DA backing pregel solution in step 2 is:
[0025] Chitosan (CS) powder was dissolved in a succinic acid (BDA) solution to obtain a CS solution. Dopamine (DA) was added to the solution with continuous stirring to obtain a CS / BDA / DA mixed solution. 1-Ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) were dissolved in deionized water and added to the prepared mixture to obtain a CS / BDA / DA pregel solution.
[0026] In some embodiments, the mass / volume ratio of the CS powder to the succinic acid solution in step 2 is 10:1, 20:1, 30:1, 40:1, or 50:1, respectively, in mg / mL; preferably 30:1.
[0027] The mass concentration of succinic acid (BDA) is 0.5%; the concentration of DA is 16 mg·mL -1 ; The stirring time is 30 min; in mg / μL, the mass / volume ratio of the EDC to deionized water is 1:2; the mass / volume ratio of the NHS to deionized water is 2:5.
[0028] In the present invention, in the specific embodiments and effect experimental investigations, the preparation method of the multifunctional cuttlebone microneedle patch in step 3 is:
[0029] Step 3.1: Mix the decalcified CBP and CMCS / Ag NPs sol with the GelMA-DA needle pregel solution, inject it into the mold, and place it in a vacuum cycle for 2 to 3 times until the solution fully fills the needle tip cavity; transfer the mold to a room temperature environment, dry and concentrate it, and cross-link it under ultraviolet light.
[0030] In step 3.2, the prefabricated backing pregel solution is injected, dried, and peeled off to obtain the multifunctional cuttlebone microneedle patch.
[0031] In some embodiments, the vacuum in step 3.1 is -0.08 MPa; the ambient temperature is 35°C; the drying and concentration time is 60 min; the ultraviolet light is 405 nm, 100 mW·cm -2 Ultraviolet light; the irradiation time is 120s.
[0032] In some embodiments, the oven drying time in step 3.2 is more than 12 hours.
[0033] Beneficial effects: Compared with the prior art, the present invention has the following beneficial effects:
[0034] This invention combines an acetic acid gradient decalcification process with a layered delivery technology to successfully construct a multifunctional, gradient-decalcified cuttlebone powder composite microneedle patch (CBP@MNs). The needles are loaded with silver nanoparticles (Ag NPs) and gradient-decalcified cuttlebone powder (CBP), and are integrated with a chitosan CS hydrogel backing layer. Through a hierarchical action pathway of "rapid sterilization-long-term repair-dynamic exudation regulation," this method achieves synergistic multi-process treatment, including antibacterial, angiogenic, and anti-inflammatory treatments, effectively improving the diabetic wound microenvironment. This approach can expand the medical applications of cuttlebone and increase its utilization. The prepared multifunctional cuttlebone microneedle patch exhibits excellent performance in multiple dimensions, promoting the repair of chronic diabetic wounds and representing a promising dressing with significant application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 (A) SEM and (B) DLS images of CBP with varying degrees of decalcification. UDCBP: undecalcified cuttlebone powder, PDCBP: partially decalcified cuttlebone powder, CDCBP: completely decalcified cuttlebone powder. Compressive properties of MNs (C) prepared with different LAP concentrations, (D) prepared with different GelMA concentrations. Swelling properties of MNs (E) prepared with different GelMA concentrations, and (F) prepared with different CS concentrations. (n = 3, *p < 0.05, **p < 0.01, ***p < 0.001, ****p < 0.0001).
[0036] Figure 2 Characterization of CBP@MNs with different degrees of decalcification (A) Micromorphology: i) Optical image ii) Side view of the needle iii) Top view SEM image of the needle, (B) In vitro release curve of CaCO3@MNs, (C) Swelling properties, EDS analysis (D) Elemental spectrum (E) Scanning image. (MNs: unloaded microneedles, UDCBP@MNs: undecalcified cuttlebone powder microneedles, PDCBP@MNs: partially decalcified cuttlebone powder microneedles, CDCBP@MNs: completely decalcified cuttlebone powder microneedles, PDCBP HG Patch: partially decalcified cuttlebone powder hydrogel patch, n=3, compared with MNs *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001; compared with CDCBP@MNs, # p<0.05);
[0037] Figure 3Cytotoxicity assay (A) L929 (B) HaCaT (C) HUVEC (MNs: unloaded microneedles, n=3), (D) hemolysis assay (n=6, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001 compared with Control). In vitro cell migration assay: (E) Microscopic images of L929 (G) HaCaT cell migration at each time point, (F) Statistics of L929 (H) HaCaT cell migration rate (UDCBP@MNs: undecalcified cuttlebone powder microneedles, PDCBP@MNs: partially decalcified cuttlebone powder microneedles, CDCBP@MNs: completely decalcified cuttlebone powder microneedles, n=3, *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001 compared with Control; compared with PDCBP@MNs, # p<0.05, ## p<0.01, ### p<0.001, #### p<0.0001). In vitro angiogenesis assay: HUVEC in vitro tube formation 48 hours after co-culture with each material group (I) Microscopic image acquisition (J) Quantitative analysis of vascular branch number (G) and tube segment length;
[0038] Figure 4 Figure 3 (A) Experimental procedures, relative residual area of wounds at each time point, (B) optical images, (C) quantitative analysis (n=5), (D) HE and Masson staining of the skin 7 and 14 days after administration: IC: Inflam cells; GT: Granulation tissue; NE: Neoepithelium; RHF: Regenerating hair follicle; CF: Collagen Fibrosis; MF: Muscle fibers; (E) Masson quantitative analysis of collagen deposition (n=3) (*p<0.05, **p<0.01, ***p<0.001, ****p<0.0001 compared with Control; compared with PDCBP@MNs, # p<0.05, ## p<0.01, ### p<0.001, #### p<0.0001). DETAILED DESCRIPTION
[0039] The present invention discloses a multifunctional cuttlebone microneedle patch and its preparation method. Those skilled in the art can refer to the contents herein and appropriately modify the process parameters to achieve the desired results. It is particularly important to note that all similar substitutions and modifications obvious to those skilled in the art are considered encompassed by the present invention. The methods and applications of the present invention have been described through preferred embodiments. It is obvious that those skilled in the art can modify, alter, and combine the methods and applications described herein to implement and apply the present invention without departing from the content, spirit, and scope of the present invention.
[0040] The disclosed embodiments are described to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is to be construed in the widest possible manner consistent with the principles and novel features disclosed herein.
[0041] The test materials used in the present invention are all common commercial products and can be purchased in the market.
[0042] The present invention is further explained below with reference to the following examples, but the examples do not limit the present invention in any form.
[0043] Example 1 Preparation and characterization of CBP, CMCS / Ag NPs sol, GelMA-DA needle pregel solution and CS / BDA / DA backing pregel solution with different decalcification degrees
[0044] 1. Decalcification of cuttlebone powder comprises the following steps:
[0045] The cuttlebone obtained from the market was air-dried and crushed into powder to facilitate full decalcification. -1 Acetic acid solutions were prepared at a ratio of 1:50 and 1:75 (m / v) with magnetic stirring overnight until no bubbles formed. The supernatant was discarded and aliquoted into 50 mL centrifuge tubes for freeze-drying. Cuttlebone powder not treated with acetic acid was designated as undecalcified sample (UDCBP); cuttlebone powder decalcified with acetic acid at a ratio of 1:50 was designated as partially decalcified sample (PDCBP); and cuttlebone powder decalcified with acetic acid at a ratio of 1:75 was designated as completely decalcified sample (CDCBP).
[0046] 2. Preparation of CMCS / AgNPs sol, including the following steps:
[0047] Prepare 15 mL of 2 × 10 -3 mol·L -1AgNO3 solution was ultrasonicated for 30 min and mechanically stirred for 4 h to prepare the precursor solution of nanosilver. 600 mg of CMCS powder was slowly added to the AgNO3 solution and mechanically stirred for 2 h. The resulting mixture was poured into a Petri dish and exposed to 100 mW·cm in a 365 nm UV curing box at a temperature below 40 °C. -2 After 30 min under UV light, CMCS / Ag NPs sol was obtained.
[0048] 3. Preparation of GelMA-DA needle pregel solution, including the following steps:
[0049] 160 mg of dopamine (DA) powder was weighed and dissolved with 500 mg, 1000 mg, 1500 mg, 2000 mg, and 3000 mg of methacryloylated gelatin (GelMA) powder in 10 mL of deionized water to obtain 5%, 10%, 15%, 20%, and 30% (w / v) GelMA-DA pregel solutions.
[0050] GelMA-DA concentration (%) = m / V0 × 100%
[0051] where V0 is the total volume of deionized water (mL), and m is the total amount of methacrylated gelatin (GelMA) powder (g).
[0052] 4. Preparation of CS / BDA / DA backing pregel solution, including the following steps:
[0053] 100 mg, 200 mg, 300 mg, 400 mg, and 500 mg of CS powder were weighed and dissolved in 10 mL of 0.5% (w / v) succinic acid (BDA) solution to obtain 1-5% (w / v) CS solutions. Subsequently, 16 mg mL -1 DA was added and stirred for 30 minutes to obtain a CS / BDA / DA mixed solution. EDC (100 mg) and NHS (80 mg) were then dissolved in 200 μL of deionized water and added to the mixed solution to obtain a CS / BDA / DA pregel solution.
[0054] 5. Scanning electron microscopy test and particle size distribution test, including the following steps:
[0055] After freeze-drying, the prepared CBP with varying degrees of decalcification were characterized using scanning electron microscopy (SEM). Each sample was attached to a conductive adhesive and sprayed with gold. The SEM was then used to observe the microscopic morphology of each sample at the appropriate angle and magnification, and images were captured.
[0056] CBP (10 mg) was added to 10 mL of ultrapure water as the dispersion medium. After ultrasonic treatment for 10 minutes to ensure uniform particle dispersion, the particle size distribution was determined using a laser particle size analyzer (Malvern Mastersizer 3000). Instrument parameters were set as follows: sample refractive index 1.55, dispersion medium refractive index 1.33, measurement range 0.01–3500 μm, and light shielding 10–20%. Each sample was measured three times, and the volume momentum mean diameter was recorded.
[0057] like Figure 1 As shown in Figure A, the degree of decalcification of cuttlebone powder significantly alters its microstructure and particle characteristics: the undecalcified sample (UDCBP) has a dense and smooth surface and a narrow particle size distribution (main peak 7.64 μm), reflecting the integrity of the mineral-organic composite structure. The partially decalcified sample (PDCBP) exhibits microcracks due to the partial dissolution of calcium carbonate, with the main particle size peak rising to 35.30 μm, reflecting moderate particle reorganization while maintaining uniform dispersion. The completely decalcified sample (CDCBP) exhibits a loose and porous structure due to the collapse of the mineral framework, with an extremely wide particle size range (1.3 to 1850 μm), indicating that heterogeneous fragmentation predominates.
[0058] like Figure 1 As shown in Figure B, undecalcified UDCBP has the smallest particle size (0.5-76 μm, main peak at 7.64 μm) and a compact and uniform distribution, indicating an intact original structure, densely packed calcium carbonate crystals, and low particle fragmentation. Partially decalcified PDCBP has a main peak rising to 35.30 μm. While still maintaining a relatively concentrated distribution, the particle size range has widened, suggesting that the decalcification process may have partially destroyed the crystal structure. While the particles undergo a certain degree of dissociation or reorganization during processing, they do not completely lose their structural regularity. Completely decalcified CDCBP has the widest particle size range (1.3-1850 μm, main peak at 66.90 μm) and a more dispersed distribution. This is likely due to the complete destruction of the original mineral structure by decalcification. After the extensive dissolution of calcium carbonate, the organic matrix and the residual inorganic phase undergo significant disparity in fragmentation, resulting in increased particle size dispersion. The uniformity of UDCBP and PDCBP is more suitable for drug delivery, while CDCBP requires process optimization to improve stability.
[0059] 6. Optimization of the component concentration of the CBP@MNs matrix material and its impact on performance, including the following steps:
[0060] The effect of the photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) concentration (0.05%-0.25%) on the mechanical properties of GelMA microneedles was systematically evaluated through an axial compression test system; the mechanical-swelling dual-effect relationship of GelMA microneedles was systematically characterized to reveal the correlation between material concentration and function; and the hygroscopic behavior of CS hydrogel was systematically evaluated through a dynamic swelling experiment system.
[0061] likeFigure 1 As shown in Figure C, when the probe displacement reaches 650μm, the ultimate compression force of the microneedle shows a significant concentration-dependent enhancement. It is worth noting that the compression force of microneedles containing ≥0.125% LAP exceeds 0.1N / needle, meeting the minimum mechanical threshold for effective penetration of the skin's stratum corneum. However, there is a trade-off between mechanical strength and biocompatibility: low-concentration LAP (0.05%-0.1%) exhibits excellent cell compatibility under visible light curing conditions, while the high-concentration (≥0.25%) group can improve mechanical properties, but the risk of cytotoxicity increases due to increased residual free radicals, which needs to be alleviated by extending the illumination time. Based on the balance between transdermal efficiency and biosafety, this study selected 0.125% LAP as the optimal concentration.
[0062] like Figure 1 As shown in D and E, the 20% GelMA microneedle achieved the best balance between mechanical strength (0.78N / needle) and swelling performance (Swelling Ratio, SR = 206.3%). Compared with the 15% GelMA group (0.24N / needle, SR = 239.7%), its mechanical properties were improved by 3.25 times, while the swelling amplitude was reduced by 14.2%. Although 30% GelMA exhibited better mechanical properties (1.16N / needle), its significantly reduced swelling capacity (SR = 148.0%) may affect drug diffusion kinetics. Therefore, in order to maintain a balance between mechanical strength and swelling performance, this experiment selected 20% GelMA as the preferred concentration of the needle matrix material for subsequent experiments.
[0063] like Figure 1 As shown in Figure F, the swelling rate of the 3% CS group was significantly higher than that of the other concentration groups (p < 0.001), so 3% CS was selected as the optimal concentration of the backing matrix material in this study.
[0064] Example 2 Preparation and Characterization of a Multifunctional Cuttlebone Microneedle Patch CBP@MNs
[0065] Through the screening of the above Example 1, the preparation method includes the following steps:
[0066] (1) Partially decalcified cuttlebone decalcified powder CBP:
[0067] The cuttlebone obtained from the market was air-dried and crushed into powder to facilitate the complete decalcification. -1 The acetic acid solution was mixed at a ratio of 1:50 (m / v) and stirred magnetically overnight until no bubbles were generated. The supernatant was discarded and aliquoted into 50 mL centrifuge tubes for freeze drying to obtain PDCBP for later use.
[0068] (2) Preparation of CMCS / AgNPs sol, including the following steps:
[0069] Prepare 15 mL of 2 × 10 -3 mol·L -1 AgNO3 solution was ultrasonicated for 30 min and mechanically stirred for 4 h to prepare the precursor solution of nanosilver. 600 mg of CMCS powder was slowly added to the AgNO3 solution and mechanically stirred for 2 h. The resulting mixture was poured into a Petri dish and exposed to 100 mW·cm in a 365 nm UV curing box at a temperature below 40 °C. -2 After 30 min under UV light, CMCS / Ag NPs sol was obtained.
[0070] (3) Preparation of GelMA-DA needle pregel solution, including the following steps:
[0071] 160 mg of DA powder and 2000 mg of GelMA powder were weighed and dissolved in 10 mL of deionized water to obtain a 20% (w / v) GelMA-DA pregel solution.
[0072] (4) Preparation of CS / BDA / DA backing pregel solution, including the following steps:
[0073] 300 mg of CS powder was weighed and dissolved in 10 mL of 0.5% (w / v) succinic acid (BDA) solution to obtain a 3% (w / v) CS solution. Subsequently, 16 mg mL -1 DA was added and stirred for 30 minutes to obtain a CS / BDA / DA mixed solution. EDC (100 mg) and NHS (80 mg) were then dissolved in 200 μL of deionized water and added to the mixed solution to obtain a CS / BDA / DA pregel solution.
[0074] (5) Molding of CBP@MNs microneedles:
[0075] 20% GelMA-DA needle pregel solution (containing 0.125% LAP) was mixed with AgNPs / CMCS sol (3:1 volume ratio), and 50 mg mL -1 The cuttlebone samples were divided into four groups according to the degree of decalcification of the added samples: the blank microneedle group was the one without the addition of cuttlebone samples; the undecalcified drug-loaded microneedles (UDCBP@MNs) were the ones with the addition of undecalcified samples (UDCBP); the partially decalcified drug-loaded microneedles (PDCBP@MNs) were the ones with the addition of partially decalcified samples (PDCBP); and the completely decalcified drug-loaded microneedles (CDCBP@MNs) were the ones with the addition of completely decalcified samples (CDCBP).
[0076] After injecting the mixed solution into the mold, the mold was placed in a vacuum (-0.08 MPa) for 3 cycles of 10 min each, with 5 min intervals for static standing, until the solution filled the needle tip cavity and no visible bubbles were present. Subsequently, the mold was transferred to a 35 °C drying oven for about 60 min, and the preliminary crosslinking of the needle body was completed by irradiation under 405 nm ultraviolet light (100 mW cm -2 ) for 120 s. Then, the pre-prepared backing pre-gel solution was injected to cover the surface of the mold with a thickness of 1 mm, and the mold was dried in an oven for more than 12 h. The microneedle array was obtained by gently peeling off the mold.
[0077] 2. Scanning electron microscopy test of CBP@MNs
[0078] After the prepared MNs were subjected to freeze-drying treatment, the morphology was characterized by scanning electron microscopy (SEM). After each group of samples was sprayed with gold on the conductive glue, the appropriate angle and magnification were found by SEM to observe the microstructure of each group of samples and take pictures.
[0079] As shown in Figure 2 A, the array of the obtained MN patch was 15 x 15, the needle body was conical, the single needle height was about 650 μm, the diameter was 300 μm, and the needle tip spacing was 700 μm.
[0080] 3. In vitro release test of CBP@MNs
[0081] In order to study the drug responsive release behavior of MNs, CaCO3 was loaded into the MN needle body material as a model drug to simulate the release of sea squirt powder. The CaCO3@MN was immersed in PBS (10 mL) and incubated at 37 °C at 100 rpm. At 30 min, 1 h, 2 h, 3 h, 6 h, 9 h, 12 h, 1 d, 2 d, 3 d, 4 d, 5 d, 6 d, and 7 d, 1 mL of the extraction solution was taken and 1 mL of PBS was added. The release of CaCO3 at each time point was measured using a soft water low hardness determination kit.
[0082] Cumulative release (%) = [(V0xC t + V∑C i ) x 100%] / m
[0083] Where V0is the total volume of the release medium, C t is the concentration of the drug in the release medium at the last sampling time point (μg mL -1 ). V is the volume of each sampling, and ∑C i is the sum of the concentrations of the drug in the release medium from the first sampling time point to the last sampling time point, and m is the total amount of the drug in the drug preparation (mg).
[0084] As shown inFigure 2 As shown in Figure B, the in vitro release of CaCO3@MN showed a significant three-stage characteristic: initial (days 1-3) rapid release (33.81±4.14%-77.15%±5.33%), indicating that the high hydrophilicity of the material or the open pore structure may accelerate the rapid diffusion and release of CaCO3 from the microneedle surface or shallow pores; the growth rate slowed down in the middle period (days 3-5) (91.12±3.73% on the 5th day), which may be limited by the internal diffusion resistance after the matrix swelling equilibrium; the release rate reached 94.08±1.21% on the 6th day, due to the disintegration of the matrix caused by material degradation and the complete dissolution of the residual components, making it close to complete release.
[0085] 4. Swelling properties of CBP@MNs
[0086] Initially, the microneedles were weighed (W0) and then immersed in 37°C PBS (pH 7.4). The swollen microneedles were removed at predetermined time intervals (1 min, 10 min, 30 min, 60 min, and 120 min), wiped dry, and weighed (Wt). Three independent samples were tested at different time intervals for each group, and the swelling rate of each microneedle in PBS was calculated using the following formula:
[0087] Swelling Ratio (SR) = (W t -W0) / W0×100%
[0088] (W0 is the initial weight of the sample, W t is the weight of the sample at a certain time point after swelling)
[0089] like Figure 2 As shown in Figure C, all groups rapidly reached swelling equilibrium within 10-30 minutes in PBS. There was no significant difference in swelling rate between the MNs group and the patch group (p>0.05), indicating that the needle structure had a limited effect on the material's swelling properties. Notably, the swelling rate of the CBP@MNs group was significantly increased, ranging from 173.0±1.15% to 180.7±4.16% (p<0.0001), compared to the MNs group (120.3%). This is likely due to the synergistic effect of the CBP's internal porous structure and high specific surface area, which significantly enhanced its fluid absorption capacity, providing a materials science foundation for wound exudate management.
[0090] 5. EDS element distribution test of CBP@MNs
[0091] The elemental composition of drug-loaded microneedles from cuttlebone powder at varying degrees of decalcification was analyzed using EDS combined with field-emission scanning electron microscopy (FE-SEM) and a silicon drift detector (SDD). The drug-loaded microneedles were freeze-dried and then gold-sprayed for analysis of C, N, O, P, Ca, and Ag.
[0092] like Figure 2 As shown in D and E, the calcium content decreased significantly with the degree of decalcification, confirming that acetic acid can effectively remove the mineral phase; Ag element was only detected in the decalcified microneedles (PDCBP@MNs 0.06wt%, CDCBP@MNs 0.05wt%), indicating that the density of the mineral structure may hinder the dispersion of Ag NPs in PDCBP@MNs; the content of organic elements such as C (45-56wt%), O (33-37wt%), and N (4-18wt%) was stable, indicating that the GelMA / CS matrix maintained structural consistency during the decalcification process.
[0093] Example 3 Biocompatibility and Angiogenesis Evaluation
[0094] 1. Biocompatibility evaluation
[0095] After blood collection was completed in strict accordance with international experimental animal ethics standards, the anticoagulant (sodium heparin) tube containing fresh mouse blood was centrifuged at 1000 rpm for 10 minutes to obtain blood cells. After washing with PBS three times, the blood cells were diluted 20 times with PBS as a red blood cell suspension for later use. The test material MNs was placed in a 24-well plate. Except for the positive control group, which added 600 μL of 0.1% Triton X-100 and 600 μL of red blood cell suspension, the remaining groups added 600 μL of PBS and 600 μL of red blood cell suspension and incubated at 37 ° C with a shaking speed of 100 rpm for 1 hour. The red blood cell suspension was then transferred to a centrifuge tube and centrifuged at 1000 rpm for 10 minutes. 100 μL of supernatant was aspirated and placed in a 96-well plate, and its absorbance was measured at 540 nm. Each group was repeated 3 times, and the hemolysis rate was calculated using the following formula. The formula is as follows:
[0096] Hemolysis rate (%) = [(A p -A b ) / (A t -A b )]×100%
[0097] Among them, A p is the absorbance value of the experimental group, A b is the absorbance value of the negative control group, A t is the absorbance value of the positive control group.
[0098] like Figure 3 As shown in AD, after co-culture of L929, HaCaT, and HUVEC cells with MNs extract for 1, 3, and 5 days, the cell viability of the experimental groups was significantly higher than or equal to that of the control group, and showed a proliferation trend over time, indicating that MNs are not only non-cytotoxic, but also exhibit potential cell proliferation-promoting effects.
[0099] 2. In vitro cell proliferation evaluation
[0100] Add an appropriate amount of basal culture medium to sterilized CBP@MNs with different degrees of decalcification, place them in a cell culture incubator for 72 hours, and then remove the extract. Filter it with a 0.22μm water filter for later use. After completing the cell inoculation, replace the CBP@MNs extract. After culturing for 1 day, use a 1mL syringe to remove the extract from the wells. Add 110μL of the previously prepared CCK-8 reaction solution (basal culture medium: CCK-8 = 10:1) to the wells under dark conditions. Incubate at 37℃ in the dark for 30 minutes. Detect the OD value at 450nm and calculate the cell proliferation rate according to the following formula:
[0101] Cell proliferation rate (%) = (OD 实验组 -OD 空白组 ) / (OD 对照组 -OD 空白组 )×100%
[0102] The blank group only contained basal culture medium and CCK-8 solution, and the control group contained basal culture medium, CCK-8 solution and cells, but no extract.
[0103] like Figure 3 As shown in Figure D, after incubation with mouse red blood cells for 1 hour, the hemolysis rate of the positive control Triton X-100 was close to 100%, and that of the blank control group (Control) was close to 0; although the hemolysis rates of each experimental group (UDCBP, PDCBP, CDCBP and MNs group) were higher than that of the blank control, the actual values were all within the safety range of 5%, indicating that the material had a slight destructive effect on red blood cells, good biocompatibility, and a low risk of inducing hemolytic reactions during application, meeting the clinical safety requirements for blood-contact materials.
[0104] 3. In vitro cell migration assessment
[0105] On the back of the 24-well plate, three parallel horizontal lines were drawn in each well using a sterilized ruler. L929 and HaCaT cells were plated at a density of 5 × 10 4 Cells were seeded at a density of 100 μl / well in a 24-well plate. After culturing for 24 and 48 hours, the culture medium was aspirated and 500 μL of PBS was added. Three straight lines were drawn perpendicular to the horizontal line on the back using a 20 μL sterile pipette tip. The PBS in the wells was aspirated and the plates were washed twice with PBS to remove floating cells. 500 μL of microneedle extract was added to each well. The plates were observed and photographed under a microscope at 0, 12, and 24 hours. The scratch area was calculated using Image J software, and the scratch healing rate was calculated using the following formula:
[0106] Scratch healing rate (%) = (S0-S t ) / S0×100%
[0107] Among them, S0 is the scratch area at 0h, St is the scratch area at a specified time.
[0108] like Figure 3 As shown in E and F, the migration rate of PDCBP@MNs at 24 h (75.7±5.51%) was significantly higher than that of UDCBP@MNs (26.7±5.51%). % , p<0.0001) and CDCBP@MNs (47.7±3.51%, p<0.001) (p<0.01). HaCaT also showed a similar trend (Figure 4G,H). The migration rate of PDCBP@MN at 12 h (37.3%) was significantly better than that of UDCBP@MNs (19.0±1.15%) and CDCBP@MNs (25.0±4.58%) (p<0.05).
[0109] 4. In vitro angiogenesis assessment
[0110] Human umbilical vein endothelial cells expressing green fluorescent protein (HUVEC-GFP) were used to construct a three-dimensional angiogenesis model. 5 Cells were seeded at a density of -1 well in a 24-well plate and co-cultured with 800 μL of microneedle extract for 48 hours (37°C, 5% CO2). 24 hours before Matrigel matrix gel was plated, the sterile pipette tip and 24-well plate were pre-cooled to 4°C to maintain colloid fluidity. 20 μL of matrix gel was accurately laid in each well (operate on ice, 25 μL of colloid was aspirated in batches and added vertically to the center of the well to avoid contact with the well wall), and gelled at 37°C for 1 hour to form a uniform base. After co-culture, the cells were washed with PBS, digested with 0.25% trypsin for 3 minutes (stopped after confirming cell retraction under an inverted microscope), and 1 mL of complete culture medium containing 10% FBS was added to terminate the reaction. The cells were collected by centrifugation (1000 rpm, 5 minutes) and resuspended to 1×10 5 cells mL -1 500 μL of cell suspension was inoculated onto a pre-coated Matrigel plate and cultured at 37°C for 6 h. Endothelial cells were visualized and imaged using an inverted fluorescence microscope. The total length of tubular structures and the number of branch points were quantitatively analyzed using the Angiogenesis Analyzer plug-in in Image J software. The experiment was performed with three technical replicates and repeated three times independently.
[0111] like Figure 3As shown in Figure 1K, the PDCBP@MNs group significantly outperformed the CDCBP@MNs group in terms of both vascular branch number and total length (p<0.05). Both groups also exhibited significant angiogenic activity compared to the UDCBP@MNs and control groups (p<0.05). This trend is consistent with the cell migration results, suggesting that partial decalcification may enhance the key links of cell migration and angiogenesis in tissue repair by synergistically releasing active ingredients (such as polysaccharides) and maintaining calcium ion homeostasis.
[0112] Example 4: C57BL / 6J mouse husbandry and surgery
[0113] The patients were injected intraperitoneally with streptozotocin (STZ, 50 mg kg) on an empty stomach (fasting for more than 12 h). -1 , 5d) induced a type I diabetes model in C57BL / 6 mice, and dynamic blood glucose monitoring (fasting blood glucose measured on the 3rd, 7th, and 14th days after the last administration was ≥16.7mmol L -1 ) and two-factor stratified random grouping (blood glucose ≥ 16.7mmol L -1 The mice with successful modeling were evenly divided into 7 groups, namely, control group, partially decalcified cuttlebone powder (PDCBP) group, non-drug-loaded microneedle (MNs) group, partially decalcified cuttlebone powder hydrogel patch (PDCBP HG Patch) group, and three gradient decalcified CBP@MNs groups.
[0114] Before surgery, diabetic mice were placed in a 3% isoflurane / oxygen mixture (1 L min -1 Administer mask inhalation anesthesia until the corneal reflex disappears. After the full-thickness skin defect of 10 mm was prepared by depilatory cream treatment, 20 μL of a 1:1 mixture of S. aureus and P. aeruginosa (1.0×10 7 CFU mL -1 ) bacterial solution, covered with 3M TM Tegaderm TM The infection was sealed with a dressing for 48 hours. The materials in each group were sterilized by UV in advance and then the wounds were treated separately: the Control group was rinsed with normal saline; the PD group was topically sprinkled with powder (30 mg / piece); the microneedle group was vertically attached and pressurized for 30 seconds; the hydrogel patch group was directly applied. All interventions were fixed with sterile dressings and the dressings were changed every 72 hours. The whole experiment was carried out in an SPF environment (23±1℃, 50±5% humidity) under double-blind management, and the wound healing rate, blood sugar fluctuations and weight changes were monitored. Strict humane endpoints (blood sugar>33.3mmol L -1The mice were euthanized when the weight loss was >20% or the Wagner grade was ≥III. The wound areas were photographed on days 0, 4, 7, 10, and 14. Five mice in each group were sacrificed on days 7 and 14, and wound samples were collected, fixed, and embedded in paraffin.
[0115] like Figure 4 As shown in Figures B and C, the experimental groups demonstrated significant healing advantages on day 4 (p < 0.05). The residual wound area in the PDCBP@MNs group (47.88 ± 11.04%) was nearly 40% lower than that in the conventional powder formulation (78.17 ± 5.09%) (p < 0.0001). This is hypothesized to be due to the physical swelling effect of the hydrogel matrix, which absorbs excess exudate and maintains moderate moisture, optimizing the wound microenvironment and overcoming the exudate accumulation associated with conventional powder coatings, thereby accelerating wound edge contraction. By day 10, the wound area in the PDCBP@MNs group had further decreased to 12.50 ± 9.32%, significantly superior to the hydrogel patch group (26.84 ± 1.52%). This suggests that the mechanical penetration properties of the microneedle array can penetrate the epidermal barrier, enabling targeted delivery of active ingredients to the wound bed basal tissue, circumventing the surface retention limitations of the patch formulation. At the end of treatment, only the PDCBP@MNs group achieved near-complete wound healing (1.47±1.16%), while the other decalcified microneedle groups (UDCBP@MNs and CDCBP@MNs) still showed residual wounds. Notably, while the non-drug-loaded microneedles (MNs) group demonstrated a physical healing effect, its healing efficiency was significantly lower than that of the PDCBP@MNs group (p<0.05).
[0116] like Figure 4As shown in Figure D, PDCBP@MNs demonstrated a significant effect in promoting diabetic wound healing. HE staining of wound tissue on day 7 of treatment revealed the formation of new granulation tissue in all groups. In the PDCBP@MNs group, new epidermal and dermal structures had formed on the wound surface, and the number of inflammatory cells was significantly reduced compared to the control group, suggesting that the material may have a mitigating effect on the inflammatory response. In contrast, while the completely decalcified microneedle group (CDCBP@MNs) also promoted some epidermal cell migration, the new epidermal layer had not yet fully closed. By day 14 of treatment, the wounds in the PDCBP@MNs group had essentially completed epithelial regeneration, with the new skin forming a multilayered structure resembling normal tissue and even the rudiments of hair follicles, while the control group only formed an incomplete, thin epidermal layer. Regarding collagen formation, staining revealed the presence of numerous, well-arranged new collagen fibers in the PDCBP@MNs group on day 7. Over time, these collagen fibers gradually formed a regular network structure, gradually resembling the collagen arrangement in surrounding healthy skin. The collagen fibers in the control group were distributed in a disordered manner. Although the amount of collagen fibers in the CDCBP@MNs group was close to that in the PDCBP@MNs group, the orientation of the fibers was more chaotic, suggesting that the degree of decalcification of the material may affect the spatial arrangement of the collagen tissue.
[0117] In summary, the multifunctional cuttlebone microneedle patch provided by the present invention can significantly promote the orderly repair process of diabetic wounds from inflammation resolution, angiogenesis to collagen remodeling.
[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A multifunctional cuttlebone microneedle patch, characterized in that: It is made of two parts: the needle body layer and the backing layer: The needle body layer is composed of cuttlebone decalcified powder, carboxymethyl chitosan / silver nanoparticle sol and methacrylated gelatin-dopamine needle body pregel solution.
2. The multifunctional cuttlebone microneedle patch according to claim 1, characterized in that: The backing layer consists of chitosan, succinic acid and dopamine.
3. The method for preparing the multifunctional cuttlebone microneedle patch according to claim 1 or 2, characterized in that: The following steps are involved: Step 1: Preparation of the components of the needle body layer; Step 2: Preparation of backing layer pregel solution; Step 3: Preparation of multifunctional cuttlebone microneedle patch.
4. The preparation method according to claim 3, characterized in that The preparation method of the components of the needle body layer in step 1 is as follows: Step 1.1: The cuttlebone is air-dried and crushed, soaked in an acid solution, and magnetically stirred until no bubbles are generated. The supernatant is discarded to obtain decalcified cuttlebone powder (CBP) with different decalcification degrees. Step 1.2: Prepare AgNO3 solution in the dark, sonicate, and stir. Add carboxymethyl chitosan (CMCS) powder to the AgNO3 solution, stir, and cure with ultraviolet light to obtain carboxymethyl chitosan / silver nanoparticle sol, i.e., CMCS / Ag NPs sol. Step 1.3: Dissolve DA powder and GelMA powder in deionized water to obtain methacrylated gelatin-dopamine GelMA-DA needle pregel solution.
5. The preparation method according to claim 4, characterized in that The acid solution in step 1.1 is glacial acetic acid solution with a concentration of 0.1-0.3 mol·L -1 ; The magnetic stirring speed is 300-800 r / min; The mass / volume ratio of cuttlebone to acid solution is 1:25-1:
100.
6. The preparation method according to claim 4, characterized in that The concentration of the AgNO3 solution in step 1.2 is 1×10 -3 ~3×10 -3 mol·L -1 The ultrasonic time is 30 min; the stirring time is 4 h; after adding carboxymethyl chitosan CMCS powder, stir for 2 h; the curing environment temperature is below 40 ° C; the ultraviolet light is 365 nm, 100 mW·cm -2 UV light; curing time is 30min; In mg / mL, the mass / volume ratio of the CMCS powder and the AgNO3 solution in step 1.2 is 20:1 to 60:
1.
7. The preparation method according to claim 4, characterized in that In mg / mL, the mass / volume ratios of the DA powder and GelMA powder described in step 1.3 to deionized water are 16:1 and 50:1-300:1, respectively.
8. The preparation method according to claim 3, characterized in that The preparation method of the backing pregel solution in step 2 is as follows: Chitosan CS powder was dissolved in succinic acid BDA solution to obtain a chitosan CS solution, and dopamine DA was added to the solution with continuous stirring to obtain a backing layer chitosan / succinic acid / dopamine CS / BDA / DA mixed solution; 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide were dissolved in deionized water and added to the mixed solution prepared above to obtain a CS / BDA / DA pregel solution.
9. The preparation method according to claim 8, characterized in that In mg / mL, the mass / volume ratio of the CS powder to the BDA solution is 10:1 to 50:1; The mass concentration of the BDA solution is 0.2% to 0.8%; the DA concentration is 12 to 20 mg·mL -1 ; In mg / μL, the mass / volume ratio of the EDC to deionized water is 1:2; the mass / volume ratio of the NHS to deionized water is 2:
5.
10. The preparation method according to claim 3, characterized in that The preparation method of the multifunctional cuttlebone microneedle patch in step 3 is as follows: The decalcified CBP and CMCS / AgNPs sols were mixed with the GelMA-DA needle pregel solution, injected into the mold, and then placed in a vacuum cycle for 2 to 3 times until the solution fully filled the needle tip cavity. The mold is dried and concentrated, and cross-linked by ultraviolet radiation; injecting a prefabricated backing pregel solution, drying, and peeling off to obtain the multifunctional cuttlebone microneedle patch; The vacuum was -0.08 MPa; the temperature was 35°C; the drying and concentration time was 60 min; the UV light was 405 nm, 100 mW·cm -2 UV light; irradiation time is 120 seconds.
11. Use of the multifunctional cuttlebone microneedle patch according to claim 1 or 2 in the preparation of a drug for promoting cell proliferation, migration and angiogenesis or accelerating wound healing.
